Advancements in rapid diagnostics and genotyping of Piscirickettsia salmonis using Loop-mediated Isothermal Amplification - Isla, Adolfo; Aguilar, Marcelo; Flores-Martin, Sandra N.; Barrientos, Claudia A.; Soto-Rauch, Genaro; Mancilla-Schulz, Jorge; Almendras, Felipe; Figueroa, Jaime; Yañez, Alejandro J. (Frontiers in Microbiology, 2024)
Piscirickettsia salmonis, the causative agent of Piscirickettsiosis, represents a significant threat to the Chilean aquaculture industry, leading to substantial economic losses annually. First identified in 1989, this pathogen is divided into two genogroups, LF-89 and EM-90, with EM-90 associated with higher mortality and pathogenicity. Traditional genotyping methods, such as multiplex PCR, while effective, are constrained by their cost, equipment requirements, and the need for specialized expertise. This study validates Loop-mediated Isothermal Amplification (LAMP) as a rapid and specific alternative for diagnosing P. salmonis infections. The first LAMP assay developed targets the species-conserved tonB receptor gene (tonB-r, WP_016210144.1), enabling species-level identification of P. salmonis. Additionally, two genotyping LAMP assays were designed to differentiate between the LF-89 and EM-90 genogroups, utilizing unique coding sequences—Nitronate monooxygenase (WP_144420689.1) for LF-89 and Acid phosphatase (WP_016210154.1) for EM-90. These LAMP assays demonstrated sensitivity and specificity comparable to real-time PCR, with the added benefits of rapid results, lower costs, and simplified operation, making them particularly suitable for field use. The specificity of the assays was confirmed by testing against other salmonid pathogens, including Renibacterium salmoninarum, Vibrio ordalii, Flavobacterium psychrophilum, Tenacibaculum maritimum, and Aeromonas salmonicida, with no cross-reactivity observed. The visual detection method and the precise differentiation between genogroups further highlight LAMP’s potential as a robust diagnostic tool for aquaculture. This advancement in the detection and genotyping of P. salmonis represents a significant step forward in disease management within the aquaculture industry. The implementation of LAMP promises enhanced disease surveillance, early detection, and improved management strategies, ultimately benefiting the salmonid aquaculture sector